Biased activation of β2-AR/Gi/GRK2 signal pathway attenuated β1-AR sustained activation induced by β1-adrenergic receptor autoantibody - Hao Chen (Nature Publishing Group, 2021)
Abstract Heart failure is the terminal stage of many cardiac diseases, in which β1-adrenoceptor (β1-AR) autoantibody (β1-AA) has a causative role. By continuously activating β1-AR, β1-AA can induce cytotoxicity, leading to cardiomyocyte apoptosis and heart dysfunction. However, the mechanism underlying the persistent activation of β1-AR by β1-AA is not fully understood. Receptor endocytosis has a critical role in terminating signals over time. β2-adrenoceptor (β2-AR) is involved in the regulation of β1-AR signaling. This research aimed to clarify the mechanism of the β1-AA-induced sustained activation of β1-AR and explore the role of the β2-AR/Gi-signaling pathway in this process. The beating frequency of neonatal rat cardiomyocytes, cyclic adenosine monophosphate content, and intracellular Ca2+ levels were examined to detect the activation of β1-AA. Total internal reflection fluorescence microscopy was used to detect the endocytosis of β1-AR. ICI118551 was used to assess β2-AR/Gi function in β1-AR sustained activation induced by β1-AA in vitro and in vivo. Monoclonal β1-AA derived from a mouse hybridoma could continuously activate β1-AR. β1-AA-restricted β1-AR endocytosis, which was reversed by overexpressing the endocytosis scaffold protein β-arrestin1/2, resulting in the cessation of β1-AR signaling. β2-AR could promote β1-AR endocytosis, as demonstrated by overexpressing/interfering with β2-AR in HL-1 cells, whereas β1-AA inhibited the binding of β2-AR to β1-AR, as determined by surface plasmon resonance. ICI118551 biasedly activated the β2-AR/Gi/G protein-coupled receptor kinase 2 (GRK2) pathway, leading to the arrest of limited endocytosis and continuous activation of β1-AR by β1-AA in vitro. In vivo, ICI118551 treatment attenuated myocardial fiber rupture and left ventricular dysfunction in β1-AA-positive mice. This study showed that β1-AA continuously activated β1-AR by inhibiting receptor endocytosis. Biased activation of the β2-AR/Gi/GRK2 signaling pathway could promote β1-AR endocytosis restricted by β1-AA, terminate signal transduction, and alleviate heart damage.